2020
DOI: 10.1016/j.jqsrt.2020.107194
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations of collisional line–shape parameters and generalized spectroscopic cross-sections for rovibrational dipole lines in HD perturbed by He

Abstract: Close-coupling calculations of generalized spectroscopic cross-sections • Ab initio investigation of pressure broadening and shift coefficients • Ab initio investigation of Dicke parameters• Data for electric dipole R (j=0-5) and P (j=1-6) lines for purely rotational transitions, fundamental band and first four overtonesHighlights for Ab initio calculations of collisional line-shape parameters and generalized spectroscopic cross-sections for rovibrational dipole lines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…117. The same methodology was applied to the cases of helium-perturbed lines of HD 118,119 and D 2 . 120,121 Recently, subpercent agreement with the experimental shapes of Ar-perturbed rovibrational lines in CO was achieved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…117. The same methodology was applied to the cases of helium-perturbed lines of HD 118,119 and D 2 . 120,121 Recently, subpercent agreement with the experimental shapes of Ar-perturbed rovibrational lines in CO was achieved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The final version of this PES, BSP3 [15], which was used in this work, has improved asymptotic behavior of the H 2 -He interaction energy at large R. The quantum scattering calculations based on the BSP3 PES were recently tested on highly accurate cavity-enhanced measurements of the shapes of He-perturbed H 2 2-0 Q(1) and 3-0 S(1) lines [31] resulting in unprecedented agreement between experimental and theoretical collision-induced line shapes. Furthermore, the BSP3 PES was employed in the studies of purely rotational lines of He-perturbed isotopologues of molecular hydrogen: D 2 [47,62] and HD [63,64].…”
Section: A Ab Initio Quantum Scattering Calculationsmentioning
confidence: 99%
“…The influence of the centrifugal distortion (the J dependence of the radial coupling terms) was usually neglected in the scattering calculations for the rovibrational transitions [15,26], as it was suggested that this effect might be masked due to the large contribution from the vibrational dephasing [46]. However, it was shown recently [61,64] that if one aims for sub-percent accuracy of the line-shape parameters, the centrifugal distortion of the potential energy surface must be taken into account. Therefore, the J-dependence of the radial coupling terms A ξ,v,J,v,J (R) was included in the following analysis.…”
Section: A Ab Initio Quantum Scattering Calculationsmentioning
confidence: 99%
“…15,16,20,21,28 The O 2 -N 2 collisional system plays a benchmark role for studying the transitions occurring within single rotational levels of atmospheric molecules, the results of such studies being important for accurate modelling and calculations of ab initio line parameters for systems of atmospheric interest in Earth as well as exoplanetary studies, and populating the spectroscopic databases with high-accuracy theoretical results. So far, in this context, extensive ab initio quantum-scattering calculations of the line-shape parameters were performed for the simple systems of He-perturbed H 2 [29][30][31][32][33] and HD 34,35 , which are relevant for the atmospheres of Solar System gas giants and some types of exoplanets. Recently, these results were used to generate comprehensive beyond-Voigt line-shape parameter dataset for these two systems 36,37 that are consistent with the HI-TRAN double-power-law representation.…”
Section: Introductionmentioning
confidence: 99%